Analysis of plasmid profiles of Escherichia coli bacteria and their resistance to several antibiotics - Aldise Indah Nurdevi; Mauritz Pandapotan Marpaung (Universitas Ahmad Dahlan, 2022)
Escherichia coli is a bacteria belonging to the family Enterobacteriaceae. Escherichia coli is a harmful gram bacterium living in the digestive tract. These bacteria also live in water and soil, commonly referred to as coliform. This research aims to analyze the plasmid profile of Escherichia coli bacteria and its resistance to some antibiotics. To explore the plasmid profiles of Escherichia coli in a recent research electrophoresis gel, the antibiotic used in its resistance tests is the Amoxicillin, Tetracycline antibiotic, Ciprofloxacin, Sulfamethoxazole, and Streptomycin antibiotic. The electrophoresis results in a difference in the number of plasmid profiles with 1 to 2 ribbons of plasmid DNA different sizes from ˜1500 bp to ˜2300 bp. Antibiotic resistance tests have occurred in Amoxicillin, Ciprofloxacin, and some resistance samples to the Streptomycin antibiotic